Implementation Of A Star Algorithm In Android Based Alien Shooter Games: Implementation Of A Star Algorithm In Android Based Alien Shooter Games - Eka Febriyanto Riski; Agung Triayudi; Eri Mardiani (Jurnal Mantik, 2020)
The development of games at this time is so rapid and a part of a lifestyle. The Alien War game is a First Person Shooter (FPS) game using the first person's point of view to aim or kill an enemy in the form of an alien. The player only sees his hand and does not see the body of the character being played. This game uses the A Star method which is applied to Non-Player Character (NPC) to find the location of players. This alien war game uses the Android operating system.